Isolation and sequence of a cDNA clone for human tyrosinase that maps at the mouse c-albino locus. - Kwon, B S (1987)
Screening of a lambda gt11 human melanocyte cDNA library with antibodies against hamster tyrosinase (monophenol, L-dopa:oxygen oxidoreductase, EC 1.14.18.1) resulted in the isolation of 16 clones. The cDNA inserts from 13 of the 16 clones cross-hybridized with each other, indicating that they were from related mRNA species. One of the cDNA clones, Pmel34, detected one mRNA species with an approximate length of 2.4 kilobases that was expressed preferentially in normal and malignant melanocytes but not in other cell types. The amino acid sequence deduced from the nucleotide sequence showed that the putative human tyrosinase is composed of 548 amino acids with a molecular weight of 62,610. The deduced protein contains glycosylation sites and histidine-rich sites that could be used for copper binding. Southern blot analysis of DNA derived from newborn mice carrying lethal albino deletion mutations revealed that Pmel34 maps near or at the c-albino locus, the position of the structural gene for tyrosinase.